The Principle of Non-Intervention in Southeast Asia: ASEAN’s Approach - Uhma, Piotr (Polish Review of International and European Law, 2025)
One of the most compelling reasons to study international law is its regional dimension - the way in which the universal principles of this legal framework are interpreted, adapted, and implemented across different parts of the world. Although international law aspires to universality, in practice it often reflects local legal traditions, historical circumstances, cultural values, and the political realities of individual regions. It is precisely these regional approaches that reveal the intricate balance between sovereignty and interdependence, between universal norms and local identities.